2007
DOI: 10.1364/ol.32.000955
|View full text |Cite
|
Sign up to set email alerts
|

750 mW continuous-wave solid-state deep ultraviolet laser source at the 2537 nm transition in mercury

Abstract: A high-power continuous-wave coherent light source at 253.7 nm is described. It is based on a solid-state Yb:YAG disk laser with two successive frequency doubling stages and is capable of generating stable output powers of up to 750 mW. Spectroscopy of the 6 (1)S(0)-6 (3)P(1) transition of mercury has been demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 15 publications
0
33
0
Order By: Relevance
“…Additional studies have shown that if degradation in CLBO occurs, it appears to be reversible [33]. This is in contrast to BBO, which shows irreversible damage caused by the formation of an absorption center [28,33,34]. Therefore, by utilizing CLBO we should be able to power scale our UV output as more fundamental power becomes available without crystal degradation.…”
Section: Doubling Stagesmentioning
confidence: 99%
“…Additional studies have shown that if degradation in CLBO occurs, it appears to be reversible [33]. This is in contrast to BBO, which shows irreversible damage caused by the formation of an absorption center [28,33,34]. Therefore, by utilizing CLBO we should be able to power scale our UV output as more fundamental power becomes available without crystal degradation.…”
Section: Doubling Stagesmentioning
confidence: 99%
“…This work will be pursued when the laser returns. Similar work has been done simultaneously, as reported in [24].…”
Section: Cooling Light Sourcementioning
confidence: 56%
“…The two photon spectroscopy techniques developed our collaborators at Gärching for hydrogen spectroscopy have revolutionized spectroscopy and laser frequency measurements. A continuous and coherent source of Lyman alpha radiation has also been developed just for these experiments [18,19,20,21]. Optics and techniques for this portion of the electromagnetic spectrum are of great interest because of possible utility for producingand probing smaller structures.…”
Section: Technological Spinoffsmentioning
confidence: 99%